Perancangan Interior Hotel Grand Cempaka Resort And Convention Di Tamansari Bogor Dengan Pendekatan Lokalitas - Utami Kusuma, Dwi; Sarihati, Titihan; Puspa Nabila, Ganesha (eProceedings of Art & Design, 2024)
In recent years, Bogor has seen an increase in the number of tourists coming to the city, which creates significant opportunities for the accommodation sector. Lodging accommodations are needed for such needs, hence the construction of a new branch of lodging accommodations in Tamansari. The area is well known for its natural beauty and cultural heritage. However, several issues arose when planning this new branch. First, there is no concept of locality in the existing interior design of Grand Cempaka Resort and Convention Hotel and similar resort hotels in the Bogor area, even though there are regulations from the government to promote the concept of locality in tourism venues. Second, there are problems in the comfort aspect of the existing hotel, which is related to sound conditioning, lighting, and ventilation. Third, there is a problem of facilities at the existing Grand Cempaka Resort and Convention Hotel which is not in accordance with 3- star hotel standards. Local government regulations emphasize the importance of local culture to increase tourism competitiveness. The design of this resort hotel has the aim that guests feel comfortable and have a different tourist experience in Bogor by using the local traditions of the Tamansari Bogor area, namely in the Sindang Barang Cultural Village, especially in the Serentaun Ceremony which is implemented in the form of interior space using the tradition transformation method, namely the ATUMICS method. Keywords: Resort Hotel, Tamansari Bogor, ATUMICS method, Sindang Barang, Serentaun Ceremony